2003
DOI: 10.4049/jimmunol.171.10.5624
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Monophasic to Recurrent Autoimmune Disease by Autoreactive T Cell Subsets

Abstract: Autoimmune uveitis has been elicited in susceptible rodents by several ocular-specific Ags. In most of these animal models the induced uveitis is acute and monophasic. Because recurrent uveitis poses the highest risk for blinding ocular complications in human disease, a spontaneous relapsing animal model would be most helpful in understanding the disease pathogenesis. In our current study we have observed that the adoptive transfer of interphotoreceptor retinoid-binding protein residues 1177–1191-specific T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 31 publications
2
35
0
Order By: Relevance
“…As we previously reported, Lewis rats immunized with the uveitogenic peptide R16 develop an acute and monophasic uveitis, showing overt clinical symptoms at 8-9 days post-immunization (p.i.) which persist for 4-5 days and subside subsequently, whereas the disease induced by adoptive transfer of in vitro activated IRBP-specific T cells develop an acute uveitis with several recurrences (Shao et al, 2003b). We found that in monophasic EAU rats, the numbers of CD8 + CD45RC low T cells were significantly increased in recovered phase of disease ( Fig.…”
Section: Cd8 + Cd45rc Low T Cells From Rats That Had Recovered From Esupporting
confidence: 48%
See 3 more Smart Citations
“…As we previously reported, Lewis rats immunized with the uveitogenic peptide R16 develop an acute and monophasic uveitis, showing overt clinical symptoms at 8-9 days post-immunization (p.i.) which persist for 4-5 days and subside subsequently, whereas the disease induced by adoptive transfer of in vitro activated IRBP-specific T cells develop an acute uveitis with several recurrences (Shao et al, 2003b). We found that in monophasic EAU rats, the numbers of CD8 + CD45RC low T cells were significantly increased in recovered phase of disease ( Fig.…”
Section: Cd8 + Cd45rc Low T Cells From Rats That Had Recovered From Esupporting
confidence: 48%
“…(Sun et al, 1988b, Sun et al, 1988a. To determine whether regulatory T cell lines express different levels of CD45RC, we compared the CD45RC expression of an encephalitogenic T cell line, S1 (Sun et al, 1988b, Sun et al, 1988a, a uveitogenic T cell line, S22 (Shao et al, 2003b), and the anti-S1 line (Sun et al, 1988b, Sun et al, 1988a. As shown in Fig.…”
Section: A Rat Regulatory T Cell Line (Anti-s1) With a Suppressive Efmentioning
confidence: 99%
See 2 more Smart Citations
“…Both the number and the activation status of autoreactive T cells are crucial for their pathogenic activity (14,17,18). In both experimental autoimmune encephalomyelitis and EAU, transfer of as few as 1 ϫ 10 6 newly activated autoreactive T cells readily induces disease, whereas transfer of 100 times as many nonactivated T cells does not (H. Shao and D. Sun, unpublished observation).…”
Section: Discussionmentioning
confidence: 99%